Physics and our world : reissue of the proceedings of a Symposium in honor of Victor F. Weisskopf - Huang, Kerson (World Scientific Publishing Company, 2014)
As the proceedings of a symposium in honor of Victor Weisskopf at MIT, this volume contains papers by leaders of physics at the time, including M. Delbrück, M. Gell-Mann, H. Bethe, T.D. Lee, B.R. Mottelson, W.K.H Panofsky, E. Purcell, J. Schwinger, S.M. Ulam, and others. Some papers address problems in the philosophy of physics, and physics and society, that are timeless in nature. But the symposium had a historical significance, in that it took place at a historic juncture of particle physics - the emergence of the Standard Model owing to experiments that point to the existence of quarks. Some of the papers reflect both the pre-quark and post-quark points of view. For these reasons, these proceedings merit reissue and reexamination.